Relaxation exercises based on pulse index and their effect on developing focus and achieving long distance bow and arrow players - م.م. فرح علاء جعفر (physical education and sport sciences college for women/ Baghdad University, 2020)
It is necessary to use relaxation exercises that help the athlete get rid of the effects of fatigue and keep the athlete away from the risk of injury and the negative effects of carrying the training, which may affect the focus of attention and achievement. Attention and the goal of the research to identify the effect of relaxation exercises according to the pulse index in developing attention concentration and achievement. The research sample was chosen from the players of the bow and arrow and the number (6) players. Because of its impact on the development process